CONSTRUCTION OF THE CONCEPT OF BUILDING POPULIST ECONOMIC LAW - Safrin Salam; Rizki Mustika Suhartono; Imron Rizki A; Mustakim La Dee (Audito Comparative Law Journal (ACLJ), 2021)
The 1945 Constitution does contain the idea of political democracy and at the same time economic democracy. That is, in the highest power holder in our country is the people, both in the political and economic fields. All political and economic resources are controlled by sovereign people. However, in a democratic system built certainly not all of them are directly controlled by the people. The purpose of this research  is  to formulate the concept of populist economic law based on economic law in Indonesia and to understand the legal comparison between Islamic economic system and conventional economic system in the development of economic law in Indonesia. This research is normative legal research that is conducted by researching and studying the laws and regulations. The research approach used in this study is 2 (two) namely statute approach and conceptual approach. The results showed that  the Concept of Economic Law Based on Populist Economy in Indonesia was built through 4 (four) principles of economic law, namely legal justice, legal certainty of benefits and affordable rules so as to realize the main goal of economic law, namely creating economic growth, balanced equality and welfare  while the Comparison of Law Between Islamic economic system and conventional economic system in economic law development in Indonesia is Islamic economy based on sharia principles while conventional economy based on human will.